Energy and the Wealth of Nations - Hall, Charles A.S.; Klitgaard, Kent (Springer, 2018)
There are four books on our shelf that have the words, more or less, “wealth of nations” in their titles. They are Adam Smith’s 1776 pioneering work, An Inquiry into the Nature and Causes of the Wealth of Nations, and three of recent vintage, David Landes’ The Wealth and Poverty of Nations, David Warsh’s Knowledge and the Wealth of Nations, and Eric Beinhocker’s The Origin of Wealth. Warsh’s book is rather supportive of current approaches to economics while Beinhocker’s is critical, but all of these titles attempt to explain, in various ways, the origin of wealth and propose how it might be increased. Curiously, none have the word “energy” or “oil” in their glossary (one trivial exception), and none even have the words “natural resources.” Adam Smith might be excused given that, in 1776, there was essentially no science developed about what energy was or how it affected other things. In an age when some 80 million barrels of oil are used daily on a global basis, however, and when any time the price of oil goes up a recession follows, how can someone write a book about economics without mentioning energy? How can economists ignore what might be the most important issue in economics? In a 1982 letter to Science magazine, Nobel Prize economist Wassily Leontief asked, “How long will researchers working in adjoining fields ... abstain from expressing serious concern about the splendid isolation within which academic economics now finds itself?” We think Leontief ’s question points to the heart of the matter. Economics, as a discipline, lives in a contrived world of its own, one connected only tangentially to what occurs in real economic systems. This book is a response to Leontief ’s question and builds a completely different, and we think much more defensible, approach to economics.
An Introduction to Biophysical Economics